Peran Posyandu dalam Meningkatkan Kualitas Kesehatan Ibu dan Anak di Jurang Asri Desa Peguyangan Kangin Denpasar - I Dewa Gede Putra Sedana; I Made Kariyana; Ni Luh Putu Ening Permini; Ni Wayan Aprilia Dwiyanti Saputri (Lembaga Pengembangan Kinerja Dosen, 2024)
Posyandu is a form of Community Resource Health Effort (UKBM) which is managed from, by, for and with the community, in order to empower the community and make it easier for the community to obtain basic health services. Improving the quality of health services can be seen from the ease of obtaining services, speed and accuracy of services and affordable costs. To fulfill the provision of good services is determined by the abilities, attitudes and behavior of service officers in their interactions with the community as service recipients. The implementation of the Posyandu program did not run smoothly due to a lack of participation from the community using the service. Adequate service facilities and facilities do not necessarily make residents active in going to Posyandu. Only a small portion of the healthy behavior of mothers and children in the community are willing to implement it and obtain it through Posyandu, so the role of cadres is very influential in increasing community participation through a pick-up system and going directly into the community